2017
DOI: 10.3892/ol.2017.7044
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the mechanism of colorectal cancer metastasis using microarray analysis

Abstract: The aim of the present study was to investigate the mechanism of metastasis in colorectal cancer (CRC) using microRNA (miRNA) and mRNA expression profiles. The mRNA and miRNA expression profiles of the GSE2509 and GSE56350 datasets were obtained from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) were identified using the limma software package. The Database for Annotation, Visualization and Integrated Discovery was used to perform Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…9 In addition, a recent microarray analysis indicated that FNDC3B was highly expressed in CRC and was suggested as a prognostic and therapeutic target of CRC, which was further verified in our study. 10 FNDC3B is initially known as a modulator of differentiation of osteoblast and adipocyte. 21 Recently, the role of FNDC3B in cancer biology was emerged as the accumulating evidence indicated that FNDC3B regulated the growth and development of diversified human tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In addition, a recent microarray analysis indicated that FNDC3B was highly expressed in CRC and was suggested as a prognostic and therapeutic target of CRC, which was further verified in our study. 10 FNDC3B is initially known as a modulator of differentiation of osteoblast and adipocyte. 21 Recently, the role of FNDC3B in cancer biology was emerged as the accumulating evidence indicated that FNDC3B regulated the growth and development of diversified human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…9 An exploration of CRC mechanism using microarray analysis revealed that FNDC3B was an upregulated gene in CRC. 10 However, the biological function of FNDC3B in the growth and metastasis of CRC tumors remains indistinct.…”
Section: Introductionmentioning
confidence: 99%
“…34 Besides, pathways in cancer also play a critical role in CRC metastasis. 35 However, more research is warranted to elucidate the precise molecular mechanisms of exosomal miRNAs in mCRC.…”
Section: Discussionmentioning
confidence: 99%
“…For subtype c6, 163 DEGs (22 up-regulated and 141 down-regulated) were identified as representative genes and were enriched in glycosaminoglycan biosynthesis-heparan sulfate, tight junction, circadian rhythm, ECM-receptor interaction and so on. Glycosaminoglycans have therapeutic value in cancer [ 56 ]; tight junction whose protein claudin-2 has been reported as a potential target for CRC therapy [ 57 ]; circadian rhythm plays roles in the pathogenesis of CRC [ 58 ]; ECM-receptor interaction may play a critical role in CRC metastasis [ 59 ]. In addition, copy loss of ARHGEF28 , BIN2P2 , and SLC25A5P9 were frequent in subtype c6, which suggested that they may be the potential biomarkers.…”
Section: Discussionmentioning
confidence: 99%